ALTERNATIF KEBIJAKAN UNTUK FLY ASH AND BOTTOM ASH (STUDI KASUS: PP NO. 22 TAHUN 2021) - Ghefira Nurul Qolbi; Budhi Gunawan; Yogi Suprayogi Sugandi (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The need for electricity supply in Indonesia is increasing amid the availability of main raw materials which can be considered